Inner-shed photoexcitation of atoms and their ions: neutral and doubly ionized Sc - (:unkn) unknown (IOP PUBLISHING LTD, 1999)
The photoionization cross section of ground state Sc(2+) is calculated using our augmented many-body-perturbation theory methodology and compared with similar results for neutral Sc. The comparison shows surprising similarities and differences which give new insight into the redistribution of oscillator strength from inner shells in response to the removal of outer-shell electrons.